Analysis of Web Server Log Files: Website of Information Management Department of Hacettepe University - Mandana Mir Moftakhari (Türk Kütüphaneciliği)
Over the last decade, the importance of analysing information management systems logs has grown, because it has proved that results of the analysing log data can help developing in information system design, interface and architecture of websites. Log file analysis is one of the best ways in order to understand information-searching process of online searchers, users’ needs, interests, knowledge, and prejudices. The utilization of data collected in transaction logs of web search engines helps designers, researchers and web site managers to find complex interactions of users’ goals and behaviours to increase efficiency and effectiveness of websites. Before starting any analysis it should be observed that the log file of the web site contain enough information, otherwise analyser wouldn’t be able to create complete report. In this study we evaluate the website of Information Management Department of Hacettepe University by analysing the server log files. Results show that there is not adequate amount of information in log files which are provided by web site server. The reports which we have created have some information about users’ behaviour and need but they are not sufficient for taking ideal decisions about contents & hyperlink structure of website. It also provides that creating an extended log file is essential for the website. Finally we believe that results can be helpful to improve, redesign and create better website.